At opposite poles: How the success of the Green Party and AfD reflects the geographical and social cleavages in Germany - Christian Franz; Marcel Fratzscher; Alexander Kritikos (DIW Weekly Report, 2019)
German voters in the 2019 European election showed remarkable regional differences in their voting behavior. The Green Party surged in West German districts, while the AfD further consolidated its successes in East Germany. Investigating structural differences at the district level reveals that the Green party is particularly popular in economically strong, demographically young, and dynamic districts with solid economic structures. The AfD receives more support in economically weaker, vulnerable districts where demographics skew toward the older population because younger people have moved away. The strength of both the Green Party and the AfD is less due to current economic growth, but rather structural and demographic factors. Thus, the Green Party and the AfD reflect polarities not only in the political arena, but also in Germany's new social divide at the district level.
Keywords: D72; Z13; 330; political parties; elections; Germany; economy; demography; structural data; European elections; Federal elections